Đánh giá chương trình đào tạo ngành Sư phạm tiếng Anh từ phản hồi của cựu sinh viên: Nghiên cứu tại Trường Đại học Đồng Tháp - Phan Ngọc Thạch , Phan Ngọc Thạch (Tạp chí Giáo dục, 2026)
In the process of implementing the English teacher education curriculum at Dong Thap University, reviewing and adjusting the curriculum, and surveying and getting feedback from stakeholders are required. In this process, alumni play both the role of learners and the bridge between the program and employers. Their feedback is highly significant for curriculum adjustments. This study presents the results of a survey of 52 alumni regarding the English Teacher Education Curriculum at Dong Thap University through questionnaires and in-depth interviews. The results show that alumni highly rate the curriculum at Dong Thap University, while also highlighting areas for improvement from the learner's perspective related to learning outcomes, curriculum content, and assessment. To improve the English Teacher Education Curriculum, it is necessary to ensure consistency between learning outcomes, content, methods, and assessment. The program should strengthen professional skills modules, information technology applications, and experiential activities, especially extracurricular ones. At the same time, it is necessary to promote the proactive role of students in assessment through self-assessment and peer assessment, enabling them to make practical contributions to program improvement and development.